2017
DOI: 10.1094/pdis-04-16-0423-re
|View full text |Cite
|
Sign up to set email alerts
|

Limestone-Mediated Suppression of Fusarium Wilt in Spinach Seed Crops

Abstract: Fusarium wilt of spinach is caused by the soilborne fungus Fusarium oxysporum f. sp. spinaciae and occurs in most regions of spinach production. The disease is favored by acid soils and warm temperatures, and the fungus can survive extended periods as chlamydospores or by asymptomatic colonization of the roots of nonhost plant species. The 10- to 15-year rotation required to minimize losses to Fusarium wilt is the primary constraint on spinach seed production in the maritime Pacific Northwest, the only region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…The application of agricultural limestone increased the average pH of the 248 soils tested from 2014 to 2019 by nearly 1.0 compared to the 147 soils tested from 2010 to 2013. These results support demonstrations that the increase in soil pH resulting from increasing rates of agricultural limestone amendment increases the incidence of Verticillium wilt of spinach (du Toit et al, 2011;Gatch & du Toit, 2017). However, the soil bioassay is completed in midwinter each year, when the daylength is too short to trigger bolting of the spinach inbred lines, so that Verticillium wilt symptoms do not develop as symptoms of this disease only develop on spinach after bolting is initiated (du Toit et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…The application of agricultural limestone increased the average pH of the 248 soils tested from 2014 to 2019 by nearly 1.0 compared to the 147 soils tested from 2010 to 2013. These results support demonstrations that the increase in soil pH resulting from increasing rates of agricultural limestone amendment increases the incidence of Verticillium wilt of spinach (du Toit et al, 2011;Gatch & du Toit, 2017). However, the soil bioassay is completed in midwinter each year, when the daylength is too short to trigger bolting of the spinach inbred lines, so that Verticillium wilt symptoms do not develop as symptoms of this disease only develop on spinach after bolting is initiated (du Toit et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…The biochar-elicited increase in potting mixture pH (6.5 vs.7.3 in the non-amended control and biochar-amended treatment, respectively) may also have played a role in promoting bacterial growth 63 . Some studies have shown that different soil amendments which increase soil pH also cause decreases in soilborne diseases caused by Fusarium species 64 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning acidic soils, long-term liming helps to alleviate soil acidity, enhancing neutrophilic bacterial growth [20], microbial biomass, and soil respiration [21]. In addition, various crop systems, such as cucumber, watermelon [22], spinach [23], and tomato [24], have shown that liming effectively inhibits pathogen populations and incidence in these crops. Several studies have shown that the application of lime in sugarcane cropping systems can not only effectively alleviate soil acidification, but also improve soil nutrient status and crop productivity.…”
Section: Introductionmentioning
confidence: 99%